On the exact polynomial time algorithm for a special class of bimatrix game - Mockus, Jonas; Sabaliauskas, Martynas (Lietuvos matematikos rinkinys, 2013)
The Strategy Elimination (SE) algorithm was proposed in [2] and implemented by a sequence of Linear Programming (LP) problems. In this paper an efficient explicit solution is developed and the convergence to the Nash Equilibrium is proven.Keywords: game theory, polynomial algorithm, Nash equilibrium.
Keywords: game theory; polynomial algorithm; Nash equilibrium